JURIDICAL ANALYSIS OF THE IMPOSITION OF SEVERE PUNISHMENT ON NARCOTICS COURIERS IN THE DECISION OF THE MEDAN DISTRICT COURT NUMBER 1238/PID.SUS/2025/PN MDN - Didit Susanto; Bonanda Japatani Siregar (Jurnal Ilmu Hukum dan Keadilan, 2026)
Imposing serious penalties on narcotics couriers based on Decision Number 1238/Pid.Sus/2025/PN Mdn consist of a trial process based on Article 145 to Article 190 of the Criminal Procedure Code and a decision process based on Article 191 to 202 of the Criminal Procedure Code. Factors that influence the imposition of serious penalties on narcotics couriers in Decision Number 1238 are the quantity and type of narcotics, the role and motivation of the suspect, the involvement in organized crime, the severity and social impact, the defendant's history of actions, the honesty and cooperation of the suspect, and the threat of punishment and applicable legal provisions. The judge's legal considerations in determining serious penalties for narcotics couriers in Decision Number 1238/Pid.Sus/2025/PN Mdn are appropriate because the elements of Article 114 paragraph (1) of Law No. 35 of 2009 concerning Narcotics have been fulfilled.